Rectal syphilis - A case report - Damjanov, Dimitrije; Jocić, Tatiana; Latinović-Bošnjak, Olgica; Damjanov, Dragomir; Savić, Željka; Kosijer, Dijana; Vračarić, Vladimir; Orlić, Tihomir; Krnetić, Žarko (Vojnosanitetski pregled, 2021)
Abstract Introduction. Syphilis rarely affects anorectal region. The symptoms are nonspecific and are commonly disregarded in our country. Therefore, they pose a difficulty both for a diagnosis and for a treatment.We presented a patient with the clinical, laboratory, endoscopic and histological characteristics of rectal siphilis who was initially suspected to have inflammatory bowel disease. Case report. A 29-year-old man was hospitalized with a suspected inflammatory bowel disease, with symptoms such as frequent blood-stained diarrhea, lower abdominal pain and a loss of appetite. The physical examination showed maculopapular skin rash on the body. The ileocolonoscopic examination revealed finely granulated rectal mucosa, the loss of vascular pattern, and at 3 cm from the anal verge, an exulcerated submucosal lesion 1.2 cm in diameter, with two smaller, similar looking lesions. The histological examination of biopsies showed diffuse inflammatory-cell infiltration, with cryptitis, Paneth cell metaplasia with granuloma without caseous necrosis, which was highly suggestive of Crohn’s disease. The Treponema pallidum test results were positive [hemagglutination assay (TPHA)] with a titer 1 : 2,560 and the rapid plasma reagin test (RPR) with a titer 1 : 16. The ensuing detailed anamnesis on the patient’s sexual behavior showed that the patient had unprotected anal sexual relation with another man and the diagnosis of secondary syphilis was confirmed. After the treatment with benzathine penicillin G once a week, during a three-week period, the patient had no symptoms and had normal inflammatory markers, with a significant decrease of RPR titre and normal mucosa on rectosigmoidoscopy. Conclusion. Taking in consideration the variable clinical and endoscopic manifestations of this disease, it is necessary to take a detailed history of sexual behavior, since it can be crucial for determining the diagnosis and differential diagnosis of siphilis.
Keywords: diagnosis, differential; homosexuality; inflammatory bowel diseases; rectal diseases; sexually transmitted diseases; syphilis; treatment outcome